262 The online Concussion Awareness Training Tool. (1st September 2016) - Babul, Shelina; Pike, Ian; Turcotte, Kate
Abstract : Background: The online Concussion Awareness Training Tool (CATT–www.cattonline.com ) includes three toolkits providing training in the recognition and treatment of concussion: Medical Professionals–MP; Parents, Players and Coaches–PPC; School Professionals–SP. Objective: To create an accessible, regularly updated online resource based upon the Zurich Consensus Statement on Concussion in Sport and evidence-based resources, intended to support standardise concussion diagnosis, treatment and management. Each toolkit includes a self-paced learning module as well as tailored resources. CATT MP aims to standardise practice in a clinical setting with a focus on the paediatric patient. CATT PPC speaks to concussion identification and management, with Smartphone accessible resources: Concussion Response Tool and Questions to Ask Your Doctor . CATT SP includes Return-to-Learn protocol and resources for teachers, counsellors and others in the school setting. Results: For each of the CATT toolkits, evaluation was undertaken with a pre-post intervention survey design. Sample sizes of at least 33 were required to compare the change in scores with the power to detect a large effect size of 0.5. CATT MP was launched mid April, 2013. Physicians demonstrated significant positive change in concussion practices (p = 0.001), and significant change in knowledge by those treating more than 10 concussions/yr (p = 0.039). Nurses had significant positive change in practices (p = 0.005) and attitudes (p = 0.035). CATT PPC was launched mid June, 2014. Parents demonstrated significant positive change in concussion knowledge (p = 0.002). CATT SP is anticipated for launch in November 2015, with an accompanying evaluation. Conclusions: Concussion is an under-diagnosed medical condition, requiring both physical and mental rest. CATT addresses this gap by increasing knowledge and awareness among appropriate audiences. Good concussion management can reduce related health problems and the risk of long-term brain damage.